(untitled) (Global Media Journal - German Edition, 2024)
Conspiracy theories present a relevant phenomenon in society and are studied within different disciplines. One of the aspects of analyzing conspiracy theories is understanding the pattern whereby social movements utilize the media to construct and spread those narratives. In that regard, social movements frame certain events as part of a conspiracy. By applying an international comparative approach, this study examines the media framing of events as a conspiracy theory in the USA and Egypt. The study focuses on political conspiracies targeting the local elite or political establishment as serving foreign enemies. Qualitative framing analysis is applied to analyze news segments (n = 140), 80 articles, and 60 videos from the Egyptian Islamist media and the Make America Great Again (MAGA) conservative media in the USA. The results show a huge similarity in the frames utilized by the media in both countries in constructing conspiracy theories. The Egyptian and American media constructed conspiracy narratives about claimed secret collusion between the elite leaders and foreign enemies. Whereas the Egyptian media morally framed the conspiracy as treason, the American media framed it as part of corruption. Moreover, the historical continuity in the Egyptian conspiracy theories was more obvious than in the theories in the USA. The empirical analysis shows that conspiracy theories are strategically used in the media to achieve certain political goals.